Giant right atrial hemangioma presenting with ascites: A case report - Salsano Antonio; Perocchio Giacomo; Guadagno Antonio; Nozza Paolo; Regesta Tommaso; Santini Francesco (Open Medicine, 2025)
Cardiac hemangiomas are slow-growing benign tumours of the heart. Patients may be asymptomatic or present a multitude of signs or symptoms.